SELFIE dla szkół – narzędzie ewaluacji wdrożenia technologii cyfrowych w szkołach - Justyna Wiśniewska; Maria Trzcińska-Król (Edukacja Ustawiczna Dorosłych, 2021)
School influences societies, shapes future citizens and employees, it is an institution that is constantly evolving. Educational programs are changed and improved, as are the competences of teachers and students, especially those necessary for living in the knowledge society. The ways of educating both students and future teachers are modified. Transformational processes require the development of a new educational paradigm, including digital technologies, team work, evaluation of current and future achievements, work efficiency, self-development of employees (teachers, management, administration employees) and management of students' learning processes. The digital transformation of schools is a complex process that requires the development of an appropriate strategy and effective methods of implementation, but also commitment and cooperation. The article presents the SEFLIE tool developed by experts of the European Commission. It allows for self-assessment and development of an action plan for the use of digital technologies in an educational institution. It is based on the European Framework for Digitally Competent Organizations (DigCompOrg). SELFIE is to provide schools with an assessment of the current use of information and communication technologies (ICT), identify the strengths and weaknesses of digitization, and assess the digital competences of teachers, students, management and other school staff. The results generated by SELFIE can be the starting point for the development of a digital strategy, which will ultimately enable an effective use of ICT tools in the teaching process.